Phytochemical Screening, Evaluation of Antioxidant and Antidiabetic Activities of Green Tea Available in Nepal - Kalauni, Surya Kant; Karki, Jeetendra; Sharma, Menaka; Khanal, Lekha Nath (Prithvi Academic Journal, 2024)
Green tea has gained popularity among consumers in recent years due to its several health benefits. It exhibits antioxidant properties, antidiabetic effects, and helpful to reduce cholesterol, stress, and anxiety. This study aims to identify the phytochemicals and assess the antioxidant and antidiabetic capacity of methanol extracts of green tea common in Nepal. The total phenolic and flavonoid contents were evaluated by Folin-Ciocalteu and aluminum chloride colorimetric methods. The antioxidant capacity was assessed using the 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging technique, while the starch-iodine method was employed to measure the α-amylase inhibition capability. Phytochemical screening showed the abundance of alkaloids, flavonoids, polyphenols, and carbohydrates in the tea. The total phenolic and flavonoid contents were 54.20 ± 1.41mg GAE/g and 91.0.50 mg QE/g respectively. The tea extract was found to show significant antioxidant and α-amylase inhibition capacities with half-maximal concentration (IC50) values of 53.79 ± 3.93 and 66.47 ± 1.94 μg/mL respectively. The outcomes of this study ratify the advantages of green tea in the management of various health issues associated to free radicals and hyperglycemia.